WEDM CUTTING OF INCONEL 718 NICKEL-BASED SUPERALLOY: EFFECTS OF CUTTING PARAMETERS ON THE CUTTING QUALITY - Caydas, Ulas; Ay, Mustafa (Inst Za Kovinske Materiale I in Tehnologie, 2016)
Investigations of the effects of machining parameters on the cutting quality of wire-electrical-discharge-machining (WEDM) cutting of an annealed Inconel 718 nickel-based superalloy are described in this paper. The cutting-quality characteristics considered are the kerf width, the recast-layer thickness and the surface roughness of the cut specimens. The essential process input parameters were identified as the pulse-on time, the pulse-peak current, and the injection pressure. The analysis of variance (ANOVA) technique was used to find the parameters affecting the cut quality. The regression analysis was used for the development of empirical models able to describe the effects of the process parameters on the quality of the WEDM cutting. The ANOVA results show that the pulse-on time and the pulse-peak current are significant variables affecting the surface roughness of wire-EDMed Inconel 718. The surface roughness, the kerf width and the recast layer of the test specimens increased as these two variables increased. The measured and modelled results were in good agreement with respect to the correlation coefficients R-a, RLT and KU.
Keywords: wire-electrical-discharge machining (WEDM); Inconel 718; recast layer; surface morphology; analysis of variance